Ranking and efficiency of the highest-quality biomedical universities. - Rosso, Annalisa; Acuti Martellucci, Cecilia; Cioni, Giovanni; Tiseo, Marco; Calò, Giovanna Letizia; Fiore, Matteo; Zauli, Enrico; Flacco, Maria Elena; Manzoli, Lamberto (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background: Academic rankings may influence student enrolment, faculty recruitment, and funding opportunities, however their methodology is often criticized, primarily because it disregards financial efficiency.Methods: We analyzed the best 100 biomedical universities in three recognized international rankings (Times Higher Education, Quacquarelli-Symonds, and Shanghai), to investigate the association between expenditure and performance. Times, Q-S and SH overall quality scores, specific sub-scores, operating expenditures, and total students’ number were extracted from official websites. A global quality score was computed as weighted mean of the three scores, and a composite efficiency score was calculated dividing the average annual expenditure per student by the global quality score.Results: Despite a general alignment, the three rankings showed several discrepancies, highlighting the potential role of a composite quality score, which showed high internal validity and reliability. Sixteen of the 20 top academies were located in USA (n=12) or UK, but the median expense per student of USA universities (183,100 USD) was more than five times larger than the European, Australian (both 28,100 USD), or Canadian (25,000 USD) centers, which showed the best efficiency scores. Indeed, greater funding was significantly associated with a higher global quality score, as well as Times, SH, Q-S scores, and most sub-scores.Discussion and Conclusions: Considering the steep differences in funding that were detected between top-ranking universities and those just below the top 40, the proposed measure of efficiency may serve as a complementary metric to recognize and reward the academies that are able to maximize resources, still delivering high-quality education.